Septic Arthritis of the Pubic Symphysis in Adult: A Case Report - Pedro José Labronici; Augusto Khede Tavares; Luiz Henrique Penteado Silva; Robinson Esteves Santos Pires; Vincenzo Giordano; Fabrício Bolpato Loures (Revista Brasileira de Ortopedia, 2021)
Abstract Septic arthritis of the pubic symphysis is a rare condition. Risk factors include trauma, low-grade infection, urological or gynecological procedures, malignant tumors of the pelvis, sports, and intravenous drug abuse. This report describes a case of septic arthritis of the pubic symphysis in a 23-year-old male patient with no history of pelvic surgery, previous infections, or intense physical activity. Arthritis was diagnosed by blood culture positive for Enterococcus spp. and yeasts, and the patient was treated with antibiotics. This case emphasizes the importance of complementary exams to aid the treatment of septic arthritis of the pubic symphysis and shows that an invasive procedure, such as pubic symphysis puncture biopsy, may not be required.